Increase the effectiveness of radar detection systems by adapting to the spatial orientation of the object of observation - S. N. Yarmolik; M. V. Svinarskiy; A. S. Khramenkov; E. V. Zaiko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
An important aspect of creation of effective recognition systems is the adaptation of radiolocation portraits to the corners of the spatial orientation of the observed object. The modeling complex for estimation of efficiency of the recognition system has been developed. Using mathematical modeling, it is shown that the utilization of adaptive range-finding radiolocation portraits of the object of observation on the basis of the most plausible estimates of its angles of spatial orientation increases of the efficiency of recognition. It is noted that in the conditions of limit of time for making decision about the class of an object, the methods of adaptation must be improved.